2012
DOI: 10.1155/2012/851941
|View full text |Cite
|
Sign up to set email alerts
|

Functional Parathyroid Cyst: A Rare Cause of Malignant Hypercalcemia with Primary Hyperparathyroidism—A Case Report and Review of the Literature

Abstract: Parathyroid cysts are rare lesions found in the neck and anterior mediastinum. They are often nonfunctional (>90%) and rarely in the functional form. This paper discusses a case of severe hypercalcemia (23 mg/dL) secondary to a rare functional parathyroid cyst. The patient was later found to have a hemorrhagic cyst with compression of the right recurrent laryngeal nerve. Preoperative diagnosis of the lesion was parathyroid carcinoma. However, reexploration of the parathyroid mass along with microscopic study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…They are commonly found in the left inferior parathyroid gland region. [3,5,7] In general they are asymptomatic; however, there may be swelling at the neck, dysphagia, odynophagia and hoarseness associated with recurrent laryngeal nerve paralysis due to the site of involvement, size and compression of the adjacent structures. Rarely, cysts located in the mediastinum may cause respiratory system symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly found in the left inferior parathyroid gland region. [3,5,7] In general they are asymptomatic; however, there may be swelling at the neck, dysphagia, odynophagia and hoarseness associated with recurrent laryngeal nerve paralysis due to the site of involvement, size and compression of the adjacent structures. Rarely, cysts located in the mediastinum may cause respiratory system symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The localization is variable between mandible and the mediastinum (3,22). Although parathyroid cysts are usually non-functioning, around 10% may secrete PTH (2) and produce a primary hyperparathyroidism (26)(27)(28). This duality suggests differences in the pathogenesis of both types of cysts.…”
Section: Discussionmentioning
confidence: 99%
“…These theories have suggested that parathyroid cysts originate from (i) embryologic remnants of the third and fourth branchial cleft; (ii) previously existing microcysts coalescing into one large cyst; (iii) simple retention of parathyroid secretions; (iv) atrophied remnants of the Kürsteiner canals of parathyroid glands of embryonic life; and (v) cystic degeneration of preexisting adenomas. [4] However, none of these theories can adequately explain the pathophysiology of parathyroid cysts on its own, and it is likely that more than one mechanism is responsible for their formation.…”
mentioning
confidence: 99%
“…[4] About 20 to 40% of cases present with signs of hyperparathyroidism and are accompanied by hypercalcemia symptoms such as nausea, vomiting, constipation, bone and joint pain, and pathological fractures. [5,6] In non-functioning cysts, due to the pressure on intra-thoracic organs, signs and symptoms such as dyspnea, dysphagia, vocal cord paralysis, or findings of thrombi caused by brachiocephalic vein or jugular vein compression are possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation